2020
DOI: 10.3892/mmr.2020.11491
|View full text |Cite
|
Sign up to set email alerts
|

Functional classification of prostate cancer‑associated miRNAs through CRISPR/Cas9‑mediated gene knockout

Abstract: The aim of the present study was to use the clustered regularly interspaced short palindromic repeats (criSPr) and criSPr-associated (cas) 9-mediated gene knockout technology for the rapid classification of the differential function of micro (mi)rnas screened using mirna expression profiling by microarray. The rational design of single guide rnas for the criSPr/Cas9 system was verified to function in human LNCaP cells with rapid and efficient target gene editing. mirna (mir)-205, mir-221, mir-222, mir-30c, mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Since the discovery of CRISPR-Cas9 in bacterial immune system [ 28 ], CRISPR-Cas9 has been adapted into a powerful tool for cancer genomic research [ 29 , 30 ]. Over the past decade, the CRISPR-Cas9 technology has become a popular technique for genome editing because it is rapid, cost-effective, precise and relatively easy to perform [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of CRISPR-Cas9 in bacterial immune system [ 28 ], CRISPR-Cas9 has been adapted into a powerful tool for cancer genomic research [ 29 , 30 ]. Over the past decade, the CRISPR-Cas9 technology has become a popular technique for genome editing because it is rapid, cost-effective, precise and relatively easy to perform [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The edited cell lines revealed that the miR21 knock-out significantly inhibited cancer cell proliferation, migration, and invasion, highlighting a prime target for cancer gene therapies ( Huo et al, 2017 ). To add to this, again using CRISPR/Cas9, Jiang et al (2020) were able to knock out several miRNA genes, including miR30c, miR205, and miR663a, in human LNCaP cell lines, and were able to determine that miR-1225-5p and miR-663a knock-outs decreased lactate production in LNCaP cells. However, although miRNA-related research is a quickly developing field with thousands of miRNAs already identified, most research has been focused on humans, and there is still much to learn.…”
Section: Crispr/cas Precision Genome Editingmentioning
confidence: 99%
“…Dzięki metodzie CRISPR możliwa jest klasyfikacja mikroRNA związanych z nowotworami. W badaniu przeprowadzonym z wykorzystaniem ludzkiej linii komórkowej raka prostaty dowiedziono, że zaburzona ekspresja dwóch miRNA (miR-663a i miR-1225-5p) wpływa na progresję raka prostaty i może być wykorzystana jako potencjalny marker tego nowotworu (28). Nabranie przez komórki nowotworowe cech komórek macierzystych jest jak dotąd słabo poznane, ale wiadomo, że wpływa to na agresywny fenotyp i oporność na leczenie.…”
Section: Wykorzystanie Technologii Crispr/cas9 W Badaniach Nad Nowotworamiunclassified